An HlyB-type function is required for expression of the Enterococcus faecalis hemolysin/bacteriocin. - Gilmore, M S (1990)
The nucleotide sequence of a 3,422-bp internal restriction fragment from the Enterococcus faecalis pAD1 hemolysin/bacteriocin-encoding region was determined. This fragment was associated with expression of hemolysin/bacteriocin component L and contained a 2,142-bp open reading frame. The inferred amino acid sequence revealed a protein which shared extensive similarity with HlyB of the Escherichia coli alpha-hemolysin operon. The inferred protein, CylB, was observed to be independently expressed in E. coli and capable of complementing an insertion mutation in the cloned hemolysin/bacteriocin operon in trans. Despite the extensive similarity to HlyB, CylB was incapable of complementing an insertion mutation in hlyB. Cytolysin determinants possessing an HlyB-type transport function are widely dispersed throughout gram-negative genera. We believe this to be the first example of an HlyB-type protein encoded within a cytolysin determinant from a gram-positive bacterium.